New frontiers in type I diabetes treatment: the impact of mesenchymal stromal cells on long-term complications - Bejugam, Deeptha; Bu, Sarah; Nguyen, Athena N.; Yaltaghian, Mariam; Smolen, Kinga K (Frontiers in Clinical Diabetes and Healthcare, 2025)
Type 1 diabetes (T1D) is not only a disorder of insulin production from beta cell destruction, but also a progressive condition that brings about life-threatening complications such as diabetic nephropathy, impaired wound recovery, and cardiovascular disease. Mesenchymal stromal cell (MSC) use has recently become an encouraging new way to treat these complications and can result in better health outcomes for T1D patients. Some research has shown that MSC injections into mice and rat models have resulted in reduced mesangial cell thickening, inflammatory mediator recruitment, proteinuria, and fibrosis normally seen in diabetic nephropathy. Other studies have demonstrated that MSCs aid wound healing by increasing anti-inflammatory M2 macrophage differentiation, stimulating angiogenesis and collagen synthesis, and signaling the proliferation and migration of dermal fibroblasts toward injury sites. Additionally, there is evidence that MSCs are capable of activating the PI3K pathway and exhibiting antioxidant effects in murine models experiencing diabetic-related heart disease. However, given these efforts, further research is needed to establish the prolonged safety and efficacy of MSC use in humans to treat T1D.